Caregivers' Impressions Predicting Fitness to Drive in Persons With Parkinson's. (January 2016) - Classen, Sherrilene; Alvarez, Liliana
Parkinson's disease (PD) is a common neurodegenerative disease, increasing in incidence, with a known impact on fitness to drive. Although great progress has been made on evidence-based guidelines for assessing fitness to drive of persons with PD, a need remains for early identification of at-risk drivers in need of comprehensive assessment. This study investigated whether caregivers of drivers with PD could predict the driver's on-road outcome. We also investigated whether the predictive value of their impressions differed from that of drivers themselves, their neurologist, or from information provided by standardized measures of visual and divided attention. Caregivers' risk impressions (odds ratio [OR] = 13.76, p = .03) and Trail Making Test Part B (Trails B; OR = 0.41, p = .02) emerged as significant predictors of passing an on-road assessment. Our findings suggest that caregiver impressions, with a measure of set shifting, may be used as an efficient screen to identify drivers with PD who are potentially at risk for failing an on-road assessment.